Conflict dynamics and local wisdom-based conflict resolution following the expansion of the new autonomous region of the Papua Mountains Province - Dafrin Muksin; Moh. Safrul Wijaya; Ikranul Sudarwan (Faculty of Social and Political Science, Universitas Airlangga, 2026)
Conflict dynamics in the Papua region have been ongoing for a long time and continue to this day. The government’s conflict management efforts have not yielded significant results, and the conflict tends to escalate. This study aims to examine the dynamics of conflict and conflict resolution based on local wisdom following the establishment of the new autonomous region (DOB) of Papua Pegunungan Province. This study uses a qualitative research type through an ethnographic approach with the research target being the Hubula Tribe Community of the Jayawijaya Regency. The research results show that the dynamics of post-DOB expansion conflicts between the government and the community are related to customary land disputes in the construction of government centers conflicts between communities often lead to inter-tribal wars triggered by territorial boundary issues, adultery, and acts of violence. This study concludes that conflict resolution using the local wisdom approach of the Hubula tribe is carried out through traditional deliberation, stone burning traditions, traditional fines, and arrow breaking rituals as a symbol of post-conflict peace. The indigenous people’s institution (LMA) plays a strategic role as a mediator in conflict resolution. The government can utilise the values of local wisdom and involve the LMA as an alternative mechanism for conflict resolution.